The impact of heterogeneous signals on stock price predictability in a rational expectations model - Christoph Winter (University of Basel, Center of Business and Economics (WWZ), 2018)
Through extending a standard Grossman and Stiglitz (1980) noisy rational expectations economy by a heterogeneous signal structure with signal-specific differences in uncertainty, we show that price momentum as well as reversal are not intrinsically at odds with rational behavior. Differences in information quality in combination with asymmetric information lead to an under- and over-reaction in equilibrium prices. We derive our results in a standard setup in which information asymmetry is mimicked by access to the realization of a certain signal including its quality, as well as in an environment in which signal quality is the only source of information asymmetry. Both scenarios support price patterns like momentum and reversal in a competitive rational expectations equilibrium without implying investor irrationality. Furthermore, we are able to show that in equilibrium it is always rational for agents to draw inference on their information sets, even in a "second-best" way. By "second best", we refer to the notion that the way in which agents process their information might result in systematic mistakes owing to the existence of asymmetric information regarding signal precision.
Keywords: D53; D82; G12; G14; 330; General Equilibrium; Asymmetric Information; Asset Pricing; Market Efficiency